The Impact of the Efficiency of Rubber Production on the Welfare of Rubber Farmers in Jambi Province - Kuswanto, Kuswanto; Alamsyah, Zulkifli; Armandelis, Armandelis; Zulfanetty, Zulfanetty (International Journal of Economics and Financial Issues, 2019)
This study aims to analyse the level of technical efficiency of rubber production and its impact on the welfare of rubber farmers in Jambi Province. The research was conducted in central area of rubber plantation in Jambi Province, namely Batanghari, Sarolangun, Tebo and Muaro Jambi. To explain the determinants of productivity and to analyse the efficiency of rubber production and the factors that influence it, the Cobb-Douglas production function model using the stochastic frozen production function approach is used. Measuring the welfare of farmers using the Farmers’ Household Income Rate (FHIR) approach. The results showed that the average rubber farmers in the study area have not been efficient in allocating inputs and not yet prosperous production. Improving the technical efficiency of rubber production through increasing the number of young farmers up to 23 percent and increasing the farming experience by 5 percent can increase the FHIR of 1.33. Keywords: household welfare, rubber farmers, technical efficiency of rubber production JEL Classifications: Q12, Q13 DOI: https://doi.org/10.32479/ijefi.7503